Evolution of a Relativistic Outflow and X-Ray Corona in the Extreme Changing-look AGN 1ES 1927+654 - Masterson, Megan; Kara, Erin; Ricci, Claudio; Garcia, Javier; Fabian, Andrew C.; Pinto, Ciro; Kosec, Peter; Remillard, Ronald A.; Loewenstein, Michael; Trakhtenbrot, Benny; Arcavi, Iair (Astrophysical Journal, 2022)
1ES 1927+654 is a paradigm-defying active galactic nucleus (AGN) and one of the most peculiar X-ray nuclear transients. In early 2018, this well-known AGN underwent a changing-look event, in which broad optical emission lines appeared and the optical flux increased. Yet, by 2018 July, the X-ray flux had dropped by over two orders of magnitude, indicating a dramatic change in the inner accretion flow. With three years of observations with NICER, XMM-Newton, and NuSTAR, we present the X-ray evolution of 1ES 1927+654, which can be broken down into three phases: (1) an early super-Eddington phase with rapid variability in X-ray luminosity and spectral parameters, (2) a stable super-Eddington phase at the peak X-ray luminosity, and (3) a steady decline back to the pre-outburst luminosity and spectral parameters. For the first time, we witnessed the formation of the X-ray corona, as the X-ray spectrum transitioned from thermally dominated to primarily Comptonized. We also track the evolution of the prominent, broad 1 keV feature in the early X-ray spectra and show that this feature can be modeled with blueshifted reflection (z = -0.33) from a single-temperature blackbody irradiating spectrum using xillverTDE, a new flavor of the xillver models. Thus, we propose that the 1 keV feature could arise from reflected emission off the base of an optically thick outflow from a geometrically thick, super-Eddington inner accretion flow, connecting the inner accretion flow with outflows launched during extreme accretion events (e.g., tidal disruption events). Lastly, we compare 1ES 1927+654 to other nuclear transients and discuss applications of xillverTDE to super-Eddington accretors.
CRIS-Team WoS Importer:2022-08-05